'Jesus, take the wheel': the appeal of spiritual products in satiating concerns about randomness. Issue 5 (24th March 2019) - Shepherd, Steven; Kay, Aaron C.
ABSTRACT: Why are consumers drawn to spiritual products? Leveraging theorising regarding the psychological need to perceive the world as orderly and non-random, we posit that products imbued with religious/spiritual significance help manage concerns about randomness and uncontrollability (e.g. when a product is unreliable or exposes the consumer to random uncontrollable processes). When randomness concerns were salient, religious consumers showed increased desire to attach religious significance to secular objects (e.g. having item blessed, physically attaching a religious symbol). For spiritual consumers, spiritual products (vs. non-spiritual physically equivalent products) were seen as having (i) non-material efficacy (i.e. efficacy not bound to the purely material world) and (ii) unfalsifiable efficacy (i.e. efficacy that is immune to contrary evidence). Evidence is found across a variety of religious and spiritual contexts.